Privatisation as a Reform Strategy of the Healthcare System in the Maldives - Mohamed, Zumlath (2009)
The purpose of this dissertation is to examine the potential implications of privatisation as a healthcare reform strategy in the Republic of Maldives. The impact of this process of privatization proposed by the government is studied in terms of its effects on quality, efficiency and accessibility of healthcare service delivery. The study being one of exploratory nature, data collection included reviewing existing literature, conducting semi structured interviews and administering a questionnaire to evaluate public opinion. Applying qualitative and quantitative analysis approaches, findings showed that privatisation of healthcare can result in improved quality and efficiency, however at a cost of increased prices in provision of healthcare. Since supporting factors such as a good health insurance scheme, regulatory and legal framework and a cost effective transport network is not in place so far, it is concluded that accessibility of healthcare services would not improve. Nevertheless, findings may bring about interesting suggestions when a larger sample from across the nation is taken and when a similar study is conducted after the privatisation has been fully implemented.